Students’ Perception towards Green Building Practices - Fitriani, Heni; Hilala, Eufrasia (Research Centre of Inorganic Materials and Complexs, 2021)
Green building practice has been gaining its popularity nowadays due to its significant benefits in protecting environment from threat caused by construction activities. It appears that there is a poor perception among construction players about green building in Indonesia. The students also play an important role in the development of construction especially green building in the future. This study aims to analyze the students’ perceptions of civil engineering and architecture students of University of Sriwijaya towards green building practices. The questionnaires were used for data collection which covered the basic understandings, criteria, benefits, and challenges of green building. There were about 240 respondents consisting of 153 from civil engineering and 87 respondents from architecture. The validity and reliability tests were conducted. The results showed that there is a positive impact on the perceptions among students towards green building adoption. Based on the analysis, the major benefit perceived by students was to reduce construction waste with a mean value of 4.67. Therefore, the reduction of construction waste will minimize the environmental damage and conserve natural resources. It was also found that the lack of knowledge from project team members about green building became the most significant challenge towards green building practices based on students’ perception. This study could offer valuable information related to benefits and challenges towards green building implementation among university students so that university could improve teaching materials and methods by applying the current issues in the construction sector.